Perancangan Sistem Informasi Website Kantor Desa Beurawe Berbasis Framework CodeIgniter - Riflansyah Riflansyah; Harry Idwan (Jurnal Manajemen Sistem Informasi (JMASIF), 2025)
The rapid development of information technology worldwide has led to the emergence of new innovations in information systems, including web-based village information systems. Beurawe Village, as part of an administrative region, requires a more efficient and accessible platform for disseminating news and public information. In response to this need, the purpose of this study is to design a website for the Beurawe Village Office to support the community in accessing information more effectively. The main issues addressed include the design of a web-based information system for village administration and the structured management of data and communication. The system aims to improve the delivery of information that can be accessed anytime and anywhere. This study applies observation, literature review, and interviews as its primary research methods. The website is developed using the CodeIgniter framework and programmed in PHP.